2016
DOI: 10.1021/acs.jpcc.6b05677
|View full text |Cite
|
Sign up to set email alerts
|

Amide III SFG Signals as a Sensitive Probe of Protein Folding at Cell Membrane Surface

Abstract: A good understanding of membrane protein folding at the molecular level requires an effective means to determine the dynamical structural changes on coil-to-helix transition within cell membrane, yet remains challenging. Herein, we demonstrate that the amide III spectral signals of protein backbone, generated in the sum frequency generation vibrational spectroscopy, are a powerful tool to probe the protein folding processes within the membrane in situ, in real time and without exogenous labels. The amide III s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 62 publications
1
44
0
Order By: Relevance
“…To discern them, we further measured the amide III signals. It has been verified that the SFG amide III signals are capable of directly distinguishing α-helix, loop, coil, and turn-like structures in proteins at interfaces. , The spectral profiles of the loop and α-helical structures were well separated in the amide III spectra which appeared below and above 1260 cm –1 , respectively . In contrast, the amide III signals of coil and turn-like structures were very weak.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…To discern them, we further measured the amide III signals. It has been verified that the SFG amide III signals are capable of directly distinguishing α-helix, loop, coil, and turn-like structures in proteins at interfaces. , The spectral profiles of the loop and α-helical structures were well separated in the amide III spectra which appeared below and above 1260 cm –1 , respectively . In contrast, the amide III signals of coil and turn-like structures were very weak.…”
Section: Resultsmentioning
confidence: 87%
“…However, this expectation is opposite to what we have observed. Earlier studies indicated that for the α-helical structure, even if the amide I signal is much weaker than the intensity of the 1660 cm –1 peak (as shown in Figure A at 1 min), the amide III signals can still be detected. , For example, in Figure B, even if the amide I signal of GP41 in the POPG bilayer at 1660 cm –1 is 5 times weaker than that of hIAPP in the DPPG bilayer, the amide III signal at 1290 cm –1 can be clearly detected for GP41; this is because the GP41 aggregation involves α-helical intermediates . In addition, this detected signal is also supported by the controlled experiments on the interaction between rat-IAPP and the DPPG lipid bilayer.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…SFG vibrational spectroscopy as a surface sensitive technique has been widely used to study chemical and biological molecules on the surface or interface. SFG theory and experimental details have been extensively reported and will not be repeated here. In this study, SFG experiments were performed using a commercial SFG system from EKSPLA.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…1). The prism-cleaning and lipid monolayer/bilayer preparations were performed using a standard procedure given previously [31][32][33][34].…”
Section: A Materials and Sample Preparationsmentioning
confidence: 99%